Analysis of The Impact of Social Media Marketing on Purchase Decisions with Brand Awareness as A Mediating Variable: A Study on MySkill.ID - Oktori Kiswati Zaini; Muhammad Fahran Januar; Aditya Prima Yudha (Journal of Social Transformation and Regional Development, 2024)
This study aims to determine the effect of the impact of social media marketing on purchasing decisions with the mediating variable of brand awareness. This type of research is explanatory research which explains the causal relationship between variables through hypothesis testing. This study used a sample of 105 respondents with the Nonprobabilty sampling method and quota sampling technique. Data analysis in this study is Partial Least Square (PLS) technique. The test results can be concluded that social media marketing has a significant direct influence on brand awareness. Brand awareness has a significant direct influence on purchasing decisions. On the other hand, social media marketing does not have a significant direct influence on purchasing decisions. Brand awareness mediates social media marketing on purchasing decisions.